The Influence Of Mozart Classical Music Therapy With Favorite Music Therapy To The Level Of Depression Of The Final Assignment Sudents Of S-1 Fisiotherapy At Health Science Faculty Of University Muhammadiyah Surakarta - Az-Zahra, Mufidah, Dwi Kurniawati, SSt.FT,M.Kes, Agus Widodo, S.Fis, M.Fis (2016)
Background: Final task (thesis) is one of role to student for graduated degree. but when the student were doing process the thesis, they had any problem like make the title, collected data until examination of thesis. This condition made the student suffer depression. One therapy for help the student to reduced depression was by using therapy music, including Mozart classical music therapy with favorite music therapy like pop music and keroncong music. Objective: To know differences from mozart classical music therapy with favorite music therapy for depression of students final task in University Muhammadiyah Surkarta. Method : The research use quasy experimental with pre test post test with control group. The sample were 27 undergraduate degree physiotherapy students whom suffer depression. Respondents divided into 12 respondents for classical music therapy, and 15 respondents in music fondness therapy. Music Therapy done 9 times for two weeks. Analysis data was using test paired sample test and independent sample test. Results: The group of music classical based on paired sample test for depression degree obtained value p = 0,000 . music fondness therapy based on paired sample test depression degree obtained value p = 0,000. Based on the different influence between therapy music and music favorite on depression degree obtained value p = 0,002. Conclusions: There is significant effect of classical Mozart music therapy to student depression. there is significant effect of favorite music therapy to student depression. There is a difference effect between Mozart classical music therapy with fondness music therapy on depression. music fondness Therapy more effective to reduce depression